Rendu-Osler-Weber disease: a gastroenterologist’s perspective - Annalisa Tortora; Maria Elena Riccioni; Eleonora Gaetani; Veronica Ojetti; Grainne Holleran; Antonio Gasbarrini (Orphanet Journal of Rare Diseases, 2019)
Abstract Hereditary hemorrhagic teleangectasia (HHT, or Rendu-Osler-Weber disease) is a rare inherited syndrome, characterized by arterio-venous malformations (AVMs or Telangiectasia). The most important and common manifestation is nose bleeds (epistaxis). The telangiectasias (small AVMs) are most evident on the lips, tongue, buccal mucosa, face, chest, and fingers, however; large arterio-venous malformations can also occur in the lungs, liver, pancreas, or brain. Telangiectasias in the upper gastrointestinal tract are known to occur, however data regarding possible small-bowel involvement is limited due to technical difficulties in visualizing the entire gastrointestinal tract. The occurrence of AVMs in the stomach and small bowel can result in chronic bleeding and anaemia. Less frequently, this may occur due to bleeding from oesophageal varices, as patients with HHT can develop hepatic parenchymal AVMs or vascular shunts which cause hepatic cirrhosis and portal hypertension. Gastroenterologists have a crucial role in the management of these patients, however difficulties remain in the detection and management of complications of HHT in the gastrointestinal tract.